Biofeedback System for Novice Snowboarding. (2016) - Moeyersons, Benjamin; Fuss, Franz Konstantin; Tan, Adin Ming; Weizman, Yehuda
Abstract: The purpose of this project was to design a biofeedback system for beginner snowboarders. The aim was to design and build an electronic system, which analysed the load under the feet of the snowboarder and alerted the rider when more load was put on the back boot compared to the front boot. There are several stages involved in such a project including initial design phase, development of sensors, software development and testing of the product. This report details the design and fabrication processes involved in the project from initial design to working prototype. We were able to successfully design a biofeedback system for beginner snowboarders as well as test the system on the snow.